Clinical features of olfactory dysfunction in elderly patients. Issue 2 (April 2023) - Okumura, Satoshi; Saito, Takahiro; Okazaki, Ken; Fushimi, Katsuya; Tsuzuki, Kenzo
Abstract: Objective: This study aimed to investigate the causes of olfactory dysfunction (OD) and to discuss the benefits of understanding the characteristics of OD in elderly patients. Methods: A total of 4300 patients with OD who were treated at our hospital between January 1996 and December 2020 were retrospectively analyzed. There were 1833 men and 2467 women, with ages ranging from 4 to 95 years. The patients were divided into two groups: younger (less than 65 years old, n  = 2947) and elderly (65 years old or more, n  = 1353) groups. Causative diseases were chronic rhinosinusitis (CRS), post-viral (PV), post-traumatic (PT), central nervous system dysfunction (CNS), peripheral nervous system dysfunction (PNS), congenital, psychogenic, and unknown. Visual analogue scale (VAS) and olfactory detection and recognition thresholds using the T&T olfaction test were used to evaluate olfaction. The mean detection and recognition thresholds, as well as the deviation difference (the difference between the mean detection and recognition thresholds) were compared by causative disease. Results: The causative diseases in elderly group were CRS (32%), PV (28%), PT (3%), CNS (2%), and PNS (4%). OD of unknown cause was significantly more in elderly (30%) than in younger patients (12%). Olfactory detection and recognition thresholds in elderly group were significantly worse than in younger group ( p  < 0.05). The olfactory detection and recognition thresholds were not any significant differences between patients with OD of unknown cause and those with CNS. Conclusion: OD of unknown cause was predominantly observed in elderly group. The olfactory acuity of OD of unknown cause was similar to CNS OD. These findings suggest the importance of continuous follow-up due to the potential of neurodegenerative diseases in elderly OD patients.